Voltage tracking of a DC-DC buck-boost converter using Gaussian Fuzzy logic control - Omar, Gadaffi (2012)
DC - DC converters are the most widely used circuits in power electronics. They can be found in almost every electronic device nowadays, since all semiconductor components are powered by DC sources. DC-DC converter usually consists of power semiconductor devices which are operated as electronic switches. Operation of the switching devices causes the inherently nonlinear characteristic to the dc-dc converters including the buck-boost converter. Proportional-Integral-Differential (PID) controllers have been usually applied to the dc-dc converters because of their simplicity design. However, implementations of this control method to the nonlinear system such as the buck-boost converters will suffer from dynamic response for the converter output. To achieve a stable and fast response, nonlinear controller were applied to control buck-boost converters. Gaussian Fuzzy Logic Control (GFLC) was designed for the buck-boost converters. MATLAB/Simulink was used as the platform in designing both of Gaussian Fuzzy Logic and PID controllers. The controllers performance are compared based on dynamic respond of the controllers in term of settling time (ts), overshoot ratio, peak time (tp) and voltage deviations. Based on simulation results, GFLC have a superior dynamic respond performance compare to PID controller. GFLC produced 0.02% overshoot ratio, 0% voltage deviation and lower setting time (36.08ms) which is a very good dynamic respond in order to achieve desired output voltage values for buck-boost converter.